2013
DOI: 10.1097/ccm.0b013e31828a3e24
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Obstetric-Related ICU Admissions in Maryland

Abstract: Objective To define the incidence, indications, and temporal trends in obstetric-related intensive care unit (ICU) admissions Design Descriptive analysis of utilization patterns Setting All hospitals within the State of Maryland Patients All antepartum, delivery and postpartum patients who were hospitalized between 1999 and 2008 Interventions None Measurements and Main Results We identified 2,927 ICU admissions from 765,598 admissions for antepartum, delivery, or postpartum conditions using appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
150
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 27 publications
14
150
2
4
Order By: Relevance
“…Studies done so far report postpartum admissions as the majority. Some studies have reported a majority of antepartum admissions [13,20], and delivery admissions (on the day of delivery) [6,21], some studies have reported a high rate, though not the majority [10,15]. Epidemiology of antepartum admissions needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies done so far report postpartum admissions as the majority. Some studies have reported a majority of antepartum admissions [13,20], and delivery admissions (on the day of delivery) [6,21], some studies have reported a high rate, though not the majority [10,15]. Epidemiology of antepartum admissions needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…For hypertensive disorders, the range is 7-73.6 % from 24 studies , and the mean is 34.85 %. For obstetric hemorrhage, the range is 11-62.5 %, and the mean is 27.90 % from 23 studies [1][2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La proporción de ingreso a UCI encontrada durante el tiempo estudiado (0,43%) se encuentra dentro de las frecuencias referidas en la literatura (6) .…”
Section: Discussionunclassified
“…De esos ingresos, 2.927 utilizaron la UCI (0,38%); 1415 de los ingresos en la UCI se produjo durante la hospitalización para el nacimiento, mayor proporción en mujeres fueron mujeres que se encontraban los extremos de la edad reproductiva, raza negra, la tasa global de utilización de la UCI fue 419/100.000 partos, durante el periodo anteparto 162/100.000, parto 202/100.000 y 54/100.000 durante el puerperio (6) .…”
Section: Discussionunclassified